TAKING INTO ACCOUNT LIFE EXPECTANCY IN SOCIAL POLICIES - ROZEZ, Sophie (MEDECINE LEGALE DROIT MEDICAL, 2025)
Over a century, social policies aimed at the elderly have been conducted on the basis of a breakdown by age groups as per individual productive capacity. Beyond the stigma attached to such a categorisation, this approach does not allow for any considering of each and everyone’s positioning at various stages of life. Taking into account life expectancy as a concept raises new perspectives inasmuch as it adresses the case of the individual throughout life.